2, 3, 7, 8‐Tetrachlorodibenzo‐p‐dioxin (TCDD) Increases Bilirubin Formation but Hampers Quantitative Hepatic Conversion of Biliverdin to Bilirubin in Rats with Wild‐Type AH Receptor. (15th February 2014) - Niittynen, Marjo; Simanainen, Ulla; Pohjanvirta, Raimo; Sankari, Satu; Tuomisto, Jouni T.
Abstract In haem degradation, haem oxygenase‐1 (HO‐1) first cleaves haem to biliverdin, which is reduced to bilirubin by biliverdin IXα reductase (BVR‐A). The environmental pollutant 2, 3, 7, 8‐tetrachlorodibenzo‐p‐dioxin (TCDD) causes hepatic accumulation of biliverdin in moderately TCDD‐resistant line B (Kuopio) rats. Using line B and two TCDD‐sensitive rat strains, the present study set out to probe the dose–response and biochemical mechanisms of this accumulation. At 28 days after exposure to 3–300 μg/kg TCDD in line B rats, already the lowest dose of TCDD tested, 3 μg/kg, affected serum bilirubin conjugates, and after doses ≥100 μg/kg, the liver content of bilirubin, biliverdin and their conjugates (collectively 'bile pigments') as well as HO‐1 was elevated. BVR‐A activity and serum bile acids were increased only by the doses of 100 and 300 μg/kg TCDD, respectively. Biliverdin conjugates correlated best with biliverdin suggesting it to be their immediate precursor. TCDD (100 μg/kg, 10 days) increased hepatic bilirubin and biliverdin levels also in TCDD‐sensitive Long‐Evans (Turku/AB; L‐E) rats. Hepatic bilirubin and bile acids, but not biliverdin, were increased in feed‐restricted L‐E control rats. In TCDD‐sensitive line C (Kuopio) rats, 10 μg/kg of TCDD increased the body‐weight‐normalized biliary excretion of bilirubin. Altogether, the results suggest that at acutely toxic doses, TCDD induces the formation of bilirubin in rats. However, concurrently, TCDD seems to hamper the quantitative conversion of biliverdin to bilirubin in line B and L‐E rats' liver. Biliverdin conjugates are most likely formed as secondary products of biliverdin.